Retrospective Observational Study on the Outcome of Medical Treatment of Atrial Fibrillation. (September 2015) - Lotstra, R.J.; van den Broek, J.; Power, T.; Marr, C.M.; Wijnberg, I.D.
Abstract : Reasons for performing study: Atrial fibrillation is a common equine arrhythmia. Quinidine alone, or with digoxin are common treatments. Studies on outcome in Warmblood populations in which duration of the AF is often unknown are limited. Objectives: To identify the factors that are associated with the success of full treatment cardioversion with oral medication, and establish whether there are differences in these factors between institutions. Study design: Retrospective case series using patient records of Equine University Clinic of Utrecht University and Rossdales Equine Hospital, Newmarket. Methods: Forty‐nine horses treated with quinidine were identified (29 Warmbloods, 20 Thorougbreds, 1 Anglo‐Arabian). Details of signalment, history, duration physical examination and echocardiography including left atrial size and presence of mitral regurgitation were retrieved. Clinical details including mean weight, age and left atrial size were compared between clinics using independent samples t test. Association between variables and cardioconversion were evaluated in a backwards logistic regression using Akaike's information criterium (AIC) and odds ratios were calculated. Factors were sex, clinic, breed, mitral regurgitation, duration and poor performance. Covariates were age, weight and the size of the left atrium. Significance was set at 0.05. Results: Fifty‐one horses (mean age 8.8 s.d. 4.5 years) were treated with quinidine sulfate, 18 also received digoxin. Eighty per cent converted to sinus rhythm. In 8 horses the known duration was less than 3 months. The only factor associated with successful treatment was the use of digoxin in combination with quinidine sulfate (odds ratio 12.4; 95% CI 2.61 and 91.85 according to AIC analysis). Conclusions: In this retrospective case series, there is much potential for bias in the data; however, the use of digoxin in addition to quinidine was associated with improved conversion rates regardless of breed even though AF duration was unknown in most horses. Ethical animal research: Research ethics committee oversight not currently required by this conference: retrospective study of clinical records. Explicit owner informed consent for inclusion of animals in this study was not stated.Source of funding: None.Competing interests: None declared.